Potential for Utilizing Organic Waste as a Heat-Insulating Composite - Rabani, Azami; Indrawan, Roger; Sabrina, Nanda Eka; Rimantho, Dino (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
The ever-increasing global population growth has a direct impact on residential building demand, which often does not keep pace with construction growth. This condition leads to an increase in housing density and a decrease in construction quality, which contributes to excessive heat inside homes. Therefore, this research explores the use of organic waste, specifically reeds and young coconut fiber, as environmentally friendly thermal materials to reduce dependence on artificial energy and its negative impacts. The high cellulose content in reeds and the fiber in young coconut fiber is a combination that has the potential to create an effective heat absorber. Product composition material testing was carried out using a thermogun, and the results were analyzed using the one-way Analysis of Variance (ANOVA) method. This research aims to utilize the potential of organic waste to produce insulation that can reduce heat temperatures in buildings, with the hope of finding alternative materials that are more sustainable and environmentally friendly.